About approaches to creation of all-Russian quality assurance agencies register - Yuriy B. Rubin; Alexandr A. Kovalenko; Tatiana A. Semkina; Erika Yu. Soboleva (Высшее образование в России)
RF-market of service on education quality assurance and independent accreditation of universities is only entering into a phase of active development. Regulation of this market is an integral requirement of its prosperity. That is why the project developed in the framework of Federal Education Development Programme – model of All-Russian Quality Assurance Agencies Register has evoked interest not only in Russia but also of international experts in quality assurance. In Europe the quality assurance agencies actively use in their work principles of publicity and openness of assessment conducting. Their work is regulated by European Register of Quality Assurance Agencies (EQAR). In this article is described the model of All-Russian Quality Assurance Agencies Register and the ways of its implementation.